COVID-19 in a Severely Immunosuppressed Patient With Life-Threatening Eosinophilic Granulomatosis With Polyangiitis - Schramm, Markus A.; Venhoff, Nils; Wagner, Dirk; Thiel, Jens; Huzly, Daniela; Craig-Mueller, Nils; Panning, Marcus; Hengel, Hartmut; Kern, Winfried V.; Voll, Reinhard E. (Frontiers in Immunology, 2020)
Immunosuppressive therapies increase the susceptibility of patients to infections. The current pandemic with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) compels clinicians to develop recommendations for successful clinical management and surveillance of immunocompromised patients at high risk for severe disease progression. With only few case studies published on SARS-CoV-2 infection in patients with rheumatic diseases we report a 25-year-old male who developed moderate coronavirus disease 2019 (COVID-19) with fever, mild dyspnea and no major complications despite having received high-dose prednisolone, cyclophosphamide and rituximab for the treatment of highly active, life-threatening eosinophilic granulomatosis with polyangiitis (EGPA).